Challenges and Overcoming The Covid-19 Pandemic in Online Learning - Bahagia, Bahagia; Pesha, Indri; Halim, Abdul Karim; Kasim, Ahmad Mulyadi; Adhiningsih, Salfania Rahmatul; Syaepulloh, Eep (Jurnal Basicedu, 2022)
This study aims to determine the adaptation and constraints of teachers using an online-based learning system in the village of Nangkasari. The method used in this research is qualitative by using data collection through interviews and observations. Sampling was done by purposive method, that is, directly assigning teachers and parents as research samples. The results showed that there were several difficulties in online learning ranging from limitations to buying credit for parents, network constraints due to remote areas, parents experiencing economic difficulties. Parents also cannot buy online learning facilities such as cellphones. In addition, parents are busy with their work, busy taking care of their children, do not understand how to teach children at home, and cannot accompany their children to study. The strategies carried out by the teacher started from using videos related to material during online learning, singing, and inviting children to the environment.